Formation of a calcium hydrogen phosphate coating on AZ41 magnesium alloy by ultrasound-assisted chemical conversion for concrete formwork - Ye Wang; Wenxin Xiao; Kai Ma; Chaoneng Dai; Danqian Wang; Jingfeng Wang (Journal of Materials Research and Technology, 2023)
The poor anticorrosion property of magnesium alloys is one of main concerns prior to their various applications. In this study, an anticorrosive hydrogen phosphate coating was fabricated via the ultrasound-assisted chemical conversion treatment on AZ41 Mg alloy for concrete formwork. The coatings prepared by the conventional chemical conversion and hydrothermal treatment were also obtained as a comparison. Surface characterizations and electrochemical methods were carried out. Results show that the ultrasound-assisted coating obtained possesses a thickness more than 3 μm, which is thicker than the other two coatings. Moreover, the ultrasound-assisted coating presents a more homogeneous structure on the second phases, while the surface qualities of the other two coatings were significantly reduced due to the inhomogeneous CaHPO4·2H2O (DCPD) formed on the second phases in AZ41 Mg alloy. The ultrasound-assisted chemical conversion coating exhibits a good corrosion resistance even comparable to the hydrothermal coating. It exhibits a corrosion current density on the order of magnitude of 10−7 A·cm−2 even after the embedment of 96 h in the Portland cement (PC) system containing 3.5 wt% NaCl.